Prediction and control of front-end curvature in hot finish rolling process. (5th November 2015) - Lee, Kyunghun; Han, Jinqyu; Park, Joonhong; Kim, Byungmin; Ko, Daecheol
The purpose of this study is to predict the front-end curvature in hot strip finishing mills and to prevent it by controlling the rolling conditions. A theoretical model based on the slab method is developed for predicting the front-end curvature by taking into account the entrance angle of the strip, the friction condition and the back tension. To validate the developed theoretical model, the theoretically obtained curvature value is compared with the results of finite element analysis. Consequently, it is shown that the calculation results of the theoretical model are in good agreement with the measured results of the finite element analysis. Furthermore, a curvature control model based on geometrical and mathematical approaches that can reduce the front-end curvature by the control of the roll speed ratio of the upper to lower rolls is proposed. The proposed curvature control model is verified by finite element analysis, and it is shown that the front-end curvature can be reduced considerably using the proposed model. Therefore, it is concluded that the proposed control model for reducing the front-end curvature in a hot strip finishing mill can be used to improve the quality of the rolled product.